Nopal Cladode (Opuntia ficus-indica) Fiber Supplementation and Lipid Profile in Dyslipidemic Adults: A Randomized Controlled Trial. - GÓMEZ-BECERRA, KARLA IVETTE; AGUILERABARREIRO, MARÍA DE LOS ANGELES; CONTRERAS-PADILLA, MARGARITA; MARTÍNEZ-GONZÁLEZ, ÓSCAR; GARRIDO-GUERRERO, GRISSEL; RODRÍGUEZ-GARCÍA, MARIO ENRIQUE; FABELA-ILLESCAS, HÉCTOR ENRIQUE; CHÁVEZ-SERVÍN, JORGE LUIS (Current Research in Nutrition & Food Science, 2026)
Opuntia ficus-indica is a traditionally consumed cactus rich in dietary fiber and has been associated with potential hypolipidemic effects. Nevertheless, there are still few clinical investigations assessing powder made from highly mature cladodes. The effects of insoluble fiber–rich powder obtained from highly mature Opuntia ficus-indica cladodes (>1000 g) on lipid parameters in overweight or obese adults with dyslipidemia were assessed in this randomized controlled study. Thirty-five participants were randomly assigned to receive 5 g/day (G1) or 15 g/day (G2) of nopal powder combined with dietary counseling, or dietary counseling alone (control group), for 12 weeks. Dietary guidance aimed to achieve an approximate total fiber intake of 30 g/day. The nopal powder contained 49.5% total dietary fiber, predominantly insoluble. Within-group analyses showed significant reductions in total cholesterol (TC) and low-density lipoprotein cholesterol (LDL) in both supplemented groups, while high-density lipoprotein cholesterol (HDL) increased in all groups. Triglycerides (TG) levels decreased significantly in the higher-dose group and in the control group (CG). However, no statistically significant differences were observed between groups at the end of the intervention (p > 0.05). Adherence to the intervention exceeded 80%, and reported gastrointestinal effects were mild and transient. Increased dietary fiber intake during the intervention period was associated with improvements in lipid parameters. However, supplementation with nopal powder did not confer additional statistically significant benefits compared with dietary counseling alone. Nevertheless, powder derived from highly mature Opuntia ficus-indica cladodes represents a concentrated source of dietary fiber that may contribute to increasing fiber intake in populations with low habitual consumption. Further investigations involving larger sample sizes are required to clarify potential dose-dependent effects.